Epidote trace element chemistry as an exploration tool in the collahuasi district, Northern Chile - Baker,MJ; Wilkinson,JJ; Wilkinson,CC; Cooke,DR; Ireland,T (Economic Geology, 2020)
The Collahuasi district of northern Chile hosts several late Eocene-early Oligocene world-class porphyry Cu-Mo deposits, including Rosario, Ujina, and Quebrada Blanca deposits, and associated high-sulfidation epithermal mineralization at La Grande. Mineralization is hosted by intermediate to felsic intrusive and volcanic rocks of the upper Paleozoic to Lower Triassic Collahuasi Group, which experienced lower greenschist facies regional metamorphism prior to mineralization. Extensive hydrothermal alteration zones surround the porphyry and epithermal deposits, associated with hypogene ore-forming processes. However, outside of the observed sulfide halo the limits of geochemical anomalism associated with mineralization are difficult to define due to mineralogical similarities between weak, distal propylitic alteration and regional metamorphism affecting the host rocks.Recent advancements in laser ablation-inductively coupled plasma-mass spectrometry analysis of epidote from hydrothermal alteration zones around porphyry and skarn deposits have shown that low-level hypogene geochemical anomalies can be detected at distances farther from the center of mineralization than by conventional rock chip sampling. Selective analysis of propylitic epidote from the Collahuasi district indicates that anomalous concentrations of distal pathfinder elements in epidote, including As (>50 ppm), Sb (>25 ppm), Pb (>100 ppm), and Mn (>5,000 ppm), were detectable 1.5 to 4.0 km from deposit centers. Significantly, the concentrations of these trace elements in epidote were obtained from samples that contained whole-rock concentrations of <25 ppm As, <2 ppm Sb, <100 ppm Pb, and <5,000 ppm Mn. Systematic increases in Cu, Mo, and Sn concentrations in epidote near deposit centers, and corresponding decreasing As, Sb and Pb concentrations, also provide effective tools for assessing the fertility and locating the centers of porphyry mineralization. In addition, anomalous conc